“GRAPHIC ORGANIZER” AS A SCAFFOLDING TOOL TO ENHANCE THE ABILITY TO WRITE A RECOUNT TEXT OF THE TENTH GRADERS (RETAIN, 2016)
“GRAPHIC ORGANIZER” AS A SCAFFOLDING TOOL TO ENHANCE THE ABILITY TO WRITE A RECOUNT TEXT OF THE TENTH GRADERS Girda Yulian Eryanti English Education Department, Language and Arts Faculty, Surabaya State University Email: girdaeryanti@mhs.unesa.ac.id Dra. Theresia Kumalarini, M.Pd English Education Department, Language and Arts Faculty, Surabaya State University Email: Theresiakumalarini@unesa.ac.id Abstract Writing is a difficult skill since it demands the students to express their thought linearly and coherently. To overcome this problem, the teacher should give a certain technique which can help them organize their ideas. One of the techniques recommended is graphic organizer. This study aims to know if there is a significant difference of students’ writing ability after being taught by using graphic organizer. It uses quantitative pre-experimental research design. Therefore, one group pretest-posttest was used in this research. The subject is the tenth graders of SMAN 2 Sidoarjo. The students’ pretest and posttest scores are then compared. The result shows that there is a significant difference of students’ writing abilities after being taught by using graphic organizer. It was proven by the means of post-test scores which are higher than those of the pre-test whose different score reaches 7.77. Moreover, the sig (2-tailed) is 0.01 which is lower than 0.05. In addition, the implementation of graphic organizer also proves to give improvement in some writing components, i.e content, organization and language use. Keywords: Writing ability, Teaching writing, Recount text, Graphic organizer Abstrak Menulis menjadi hal yang sulit dilakukan oleh siswa ketika mereka dituntut untuk mengutarakan pemikirannya secara runtut dan jelas. Untuk mengatasi masalah ini, guru sebaiknya memberikan teknik tertentu untuk membantu siswa dalam mengorganisasi ide mereka; salah satu teknik yang disarankan adalah graphic organizer teknik. Penelitian ini bertujuan untuk mengetahui perbedaan yang signifikan terhadap kemampuan menulis siswa setelah diajarkan menggunakan graphic organizer. Penelitian ini merupakan penelitian quantitative pre-experimental. Oleh karena itu, penelitian ini menggunakan satu grup pre-test dan post-test. Subjek penelitian ini adalah siswa kelas X di SMAN 2 Sidoarjo. Nilai pre-test dan post-test siswa kemudian dibandingkan. Hasil penelitian menunjukan bahwa terdapat perbedaan yang signifikan terhadap kemampuan menulis siswa setelah diajar menggunakan graphic organizer. Hal ini dibuktikan dengan rata-rata nilai post-test yang lebih tinggi daripada nilai pre-test dengan perbedaan nilainya adalah 7.77. Nilai sig (2-tailed) adalah 0.01 dan itu lebih rendah dari 0.05. Sebagai tambahan, penerapan graphic organizer juga terbukti memberi peningkatan terhadap beberapa komponen menulis, seperti: isi, pengorganisasian, dan penggunaan bahasa. Kata Kunci: Kemampuan menulis, Pengajaran menulis, Teks recount, Graphic organizer